Synthesis and Biological Activity of Some New β-Diketone Complexes of Cr(III) - Hogale, M.B.; Khot, B.R. (Asian Journal of Chemistry, 2010)
Various substituted β-diketone complexes of Cr(III) have been synthesised and characterised on the basis of analytical, infrared, nuclear magnetic resonance, electronic spectral and magnetic susceptibility data. The antimicrobial study of the complex was made against S. aureus and E. coli. Most of them have exhibited moderate antibacterial activity. A probable correlation of activity and the structure has been established.